Case report: Difficult diagnosis of Mycobacterium tuberculosis infection in patients after allogeneic hematopoietic stem cell transplantation: two case reports and a literature review - Liu, Zhenghua; Cai, Dali; Su, Nan (Frontiers in Oncology, 2024)
Background: Mycobacterium tuberculosis (MTB) is a relatively infrequent infection encountered during hematopoietic stem cell transplantation (HSCT). The identification of MTB following HSCT remains a complex task, with delayed detection and misdiagnosis potentially resulting in unfavorable outcomes. Metagenomic next-generation sequencing (mNGS) represents a novel, highly sensitive and rapid diagnostic tool in clinical settings for discerning intricate infections and detecting exceedingly rare pathogens.Methods: With the aid of mNGS, we diagnosed MTB in the lymph nodes and lungs of two patients with hematological diseases following allogeneic peripheral blood hematopoietic stem cell transplantation. Both patients presented with fever, localized symptoms and clinical signs. Following inconclusive results from routine tests, impractical biopsy procedures and unsuccessful responses to empirical treatments, mNGS was employed as a final recourse, revealing DNA fragments of MTB in blood samples.Results:The diagnoses were ultimately confirmed in conjunction with additional clinical evidence. The application of mNGS in MTB cases after allogeneic HSCT has rarely been reported. The mNGS technique can provide a prompt and highly sensitive indication leading to the definitive diagnosis of MTB in complex post-transplant scenarios.